Percepatan Proses Adopsi Inovasi Melalui Komunikasi Inovasi Bawang Merah: Tinjauan Perspektif Cess Leeuwis - Filya Hidayati; Rahmat Syahni; Irfan Suliansyah; Hery Bachrizal Tanjung (CV.ITTC INDONESIA, 2026)
This paper aims to conceptually and empirically examine the role of two-way communication between extension workers and farmers in accelerating the adoption of shallot innovations. Adoption of agricultural innovations is a strategic element in increasing the productivity and competitiveness of horticultural commodities, but its implementation in various production centers remains suboptimal. This situation indicates that the success of innovation is determined not only by technical excellence but also by the effectiveness of the accompanying communication process. Theoretically, Rogers explains that innovation adoption proceeds through five stages: knowledge, persuasion, decision, implementation, and confirmation. At the persuasion and decision-making stages, two-way communication is crucial because farmers need a dialogue space to understand the benefits, risks, and suitability of the innovation for their farming conditions. This perspective is reinforced by Leeuwis, who asserts that agricultural innovation is the result of social construction through interaction, collective learning, and negotiation of meaning between actors. Thus, a dialogic and participatory extension approach is a prerequisite for effective innovation diffusion. This research uses a qualitative descriptive approach through a case study in a shallot production center. The results indicate that innovation communication is relatively effective, particularly through face-to-face interactions such as field demonstrations and group discussions. Farmers who engage in intensive dialogue with extension workers have a more comprehensive understanding of the characteristics of innovations, make faster adoption decisions, and are more consistent in their implementation. Conversely, one-way extension services tend to lead to hesitation and delayed adoption. Communication effectiveness is influenced by the competence of extension workers, farmer characteristics, and the availability of adequate communication channels. Therefore, strengthening participatory communication capacity and developing a dialogic extension system are important strategies for accelerating the sustainable adoption of agricultural innovations.